2015
DOI: 10.1128/aac.00761-15
|View full text |Cite
|
Sign up to set email alerts
|

GS-5806 Inhibits Pre- to Postfusion Conformational Changes of the Respiratory Syncytial Virus Fusion Protein

Abstract: b GS-5806 is a small-molecule inhibitor of human respiratory syncytial virus fusion protein-mediated viral entry. During viral entry, the fusion protein undergoes major conformational changes, resulting in fusion of the viral envelope with the host cell membrane. This process is reproduced in vitro using a purified, truncated respiratory syncytial virus (RSV) fusion protein. GS-5806 blocked these conformational changes, suggesting a possible mechanism for antiviral activity. R espiratory syncytial virus (RSV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Furthermore, our proposed mechanism is consistent with that recently proposed for GS-5806 (ref. 30), suggesting that all RSV fusion inhibitors act as antagonists of F triggering.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our proposed mechanism is consistent with that recently proposed for GS-5806 (ref. 30), suggesting that all RSV fusion inhibitors act as antagonists of F triggering.…”
Section: Discussionmentioning
confidence: 99%
“…While GS-5806 was inactive in an RSV replicon assay that measures viral RNA transcription and replication functions, it effectively inhibited cell-to-cell fusion (syncytia) mediated by RSV F protein. Evaluation of liposomes containing pretriggered RSV F protein revealed that GS-5806 inhibits the pre-to postfusion conformational change within the F protein necessary for viral fusion with the host cell membrane (41,42). Finally, drug susceptibility determinants mapped to the RSV F gene, indicating that the fusion protein is the likely target of GS-5806.…”
Section: Discussionmentioning
confidence: 99%
“…Crystallographic experiments later revealed that the small molecules bind inside the central cavity of the prefusion conformation and interact with residues in the fusion peptide and the second heptad repeat 141 . Functional studies with soluble F proteins 142 and membrane-bound F proteins 141 demonstrated that the small molecules function as antagonists that prevent The fusion (F) protein can interact with one or more attachment factors to bind the virus to the host cell, a process that is greatly enhanced by the viral attachment protein (not shown). The F protein may also interact with a functional receptor that induces refolding of the prefusion conformation to the prehairpin intermediate.…”
Section: Small-molecule Fusion Inhibitorsmentioning
confidence: 99%